Protective Roles and Mechanisms of Taurine on Myocardial Hypoxia/Reoxygenation-Induced Apoptosis - Yang, Xiaohong (Acta Cardiol Sin, 2019)
BACKGROUND: This study aimed to investigate the protective roles and mechanisms of taurine on myocardial ischemia/reperfusion (I/R)-induced cell apoptosis, and thus provide evidence for the treatment of myocardial I/R injury and the development of related drugs. METHODS: The cardiomyocytes of neonatal rats were used to prepare the hypoxia/reoxygenation (H/R) injury model; gene transfection and small interfering RNA (siRNA) target gene silencing techniques were performed, along with methyl thiazolyl tetrazolium (MTT) assay to detect cell survival, flow cytometry to detect cell apoptosis, and Western blot to measure protein expressions. RESULTS: Compared with the H/R group, the apoptosis rates of cardiomyocytes in the three taurine (TAU)-protection groups were significantly decreased (p < 0.05). As the TAU concentration increased, the expression of Bcl-2 protein in H/R cardiomyocytes also gradually increased (p < 0.05), while the protein expressions of p53 up-regulated modulator of apoptosis (PUMA), C/EBP homologous protein (CHOP), Bax, glucose-regulated protein 78kD (GRP78), and caspase-3 gradually decreased (p < 0.01). TAU strongly downregulated the expression of PUMA-transfected cardiomyocytes. After targeted silencing of PUMA, the apoptosis rate was significantly decreased, while the expression of Bcl-2 protein was increased, and that of Bax protein was decreased (p < 0.05). CONCLUSIONS: TAU significantly inhibited myocardial H/R-induced apoptosis, and the mechanism may be related to a downregulated expression of PUMA.